5G X-Cube enables the large-scale development of 5G customized network - Lei CAO; Li LI; Shengye HU; Zhimin ZHONG; Zhihui GAN; Xiaodong DONG; Bojiao MA; Tao ZHANG (Dianxin kexue, 2022)
In the current process of large-scale development of 5G customized networks, telecom operators are facing with difficulties such as difficulty in real-time response to customized needs of industrial customers and difficulty in quickly replicating benchmarking experiences on a large scale.The concept of 5G X-Cube was innovatively proposed Through the modularization and standardization of requirements, capabilities, and products, a capability body that could be combined and innovated was formed.Industrial customer needs were quickly transformed into customized network configuration parameters to achieve real-time response to 5G customization needs.As an online 5G customized network intelligent expert, 5G X-Cube applies intelligent technology to the real-time packaging of 5G solutions, leading a new path for the scale development of the 5G customized network.